KAJIAN RETORIKA YANG BERKEMBANG PADA MASA PANDEMI COVID-19 DI INDONESIA - Erfinawati Erfinawati; Ismawirna Ismawirna; Harunun Rasyid; Nisa Ayu Lestri; Eli Nurliza (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This research is one of the benchmarks for the development of rhetoric during the pandemic and provides knowledge to readers about the rhetoric and terms that developed during the 2020 Covid-19 pandemic in Indonesia.The problem posed in this study is how rhetoric developed during the 2020 Covid-19 pandemic in Indonesia. The purpose of this study is to describe data on rhetorical developments that emerged during the 2020 co-19 pandemic in Indonesia. The data sources in this study are in the form of videos that discuss Covid-19 in 2020. Data collection was carried out using observation techniques and documentation techniques. This research uses descriptive research with a qualitative approach. The data analysis technique used is a qualitative analysis technique with the stages of observing, writing, describing, and concluding data. The results of the study found that the three videos that had been examined all used aspects of rhetoric to persuade people that they fulfilled ethos, logos, and pathos when viewed from Aristotle's art of persuasion. The three videos that have been studied apply the use of five aspects in rhetoric, such as the discovery aspect, the arrangement aspect, the style aspect, the delivery aspect and the memory aspect and others and types of rhetoric including forensic rhetoric, demonstrative rhetoric and deliberative rhetoric